Epidemiology and genetic diversity of respiratory syncytial virus in adults 50 years and older with acute respiratory infections in Accra, Ghana - Antwi. C.N; Dzudzor. B.; Aboagye, J,O; et al. (BMC Infectious Diseases, 2025)
Background Human respiratory syncytial virus (RSV) is responsible for lower respiratory tract infections, particularly posing a signifcant threat to infants, the elderly, and immunocompromised individuals. However, the disease burden is poorly understood in the adult population in Africa. This molecular study investigated the occurrence of RSV in adults 50 years and older and assessed the genetic variability of circulating RSV genotypes in patients with acute respiratory tract infection (ARI) in Accra, Ghana. Methods From March to October 2023, patients who are≥50 years of age with confrmed ARI cases were enrolled from three hospitals in Accra, Ghana. Nasopharyngeal specimens were collected and analyzed for RSV using real-time quantitative PCR. The second hypervariable region of RSV-positive samples was targeted for sequencing. Bioinfor matics analysis was carried out to identify the predominant circulating genotypes and a phylogeny established between sequences from this study and other globally circulating RSV genotypes. Amino acids deduction analysis was performed to identify the genetic variability and evolution of the RSV genotypes identifed. Results A total of 212 patients were enrolled. RSV infection was confrmed in 11 (5.2%) participants. RSV infection was more prevalent among patients aged 65 years and older (8/11, 54.5%). Patients with underlying chronic diseases (18%) sufered severe medically attended RSV complications requiring intensive care and ventilation support. RSV disease wassignifcantly associated with cough (p=0.023). Phylogenetic and amino acid sequence analysis revealed RSV-B sequences clustered as BA; specifcally, the globally prevailing BA9 genotype. No cases of RSV-A were identifed. RSV/BA9 dominated the season from July to October 2023. Specifc amino acid substitutions both outside and within the duplication region of the G gene were present, and presence of individual clusters and branches provided evidence ofstrains diversifcation and evolution. Conclusion This study provides the frst baseline report of RSV disease occurrence among adults≥50 years in Ghana. It reveals the genetic diversifcation of prevailing RSV/BA9 genotypes identifed and addresses the need for continu ous RSV surveillances and targeted interventions in this frail population.
Research Article
Keywords: Respiratory syncytial virus; Acute respiratory infection; Older adults